2018
DOI: 10.1111/add.14510
|View full text |Cite
|
Sign up to set email alerts
|

How competent are people who use opioids at responding to overdoses? Qualitative analyses of actions and decisions taken during overdose emergencies

Abstract: Background and Aims Providing take-home naloxone (THN) to people who use opioids is an increasingly common strategy for reversing opioid overdose. However, implementation is hindered by doubts regarding the ability of people who use opioids to administer naloxone and respond appropriately to overdoses. We aimed to increase understanding of the competencies required and demonstrated by opioid users who had recently participated in a THN programme and were subsequently confronted with an overdose emergency. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 62 publications
5
34
0
1
Order By: Relevance
“…Overall, findings from the interviews highlight the feasibility of community-based overdose education and naloxone distribution, as participants reported high levels of accessibility and satisfaction as well as high perceived effectiveness of naloxone in reversing overdoses. These findings are consistent with other recent literature demonstrating the competence of peers in administering naloxone and reversing overdose [44] and also suggest that overdose education may be useful for overcoming opioid knowledge deficits experienced by rural individuals [45].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, findings from the interviews highlight the feasibility of community-based overdose education and naloxone distribution, as participants reported high levels of accessibility and satisfaction as well as high perceived effectiveness of naloxone in reversing overdoses. These findings are consistent with other recent literature demonstrating the competence of peers in administering naloxone and reversing overdose [44] and also suggest that overdose education may be useful for overcoming opioid knowledge deficits experienced by rural individuals [45].…”
Section: Discussionsupporting
confidence: 91%
“…As OEND programs continue to expand, research has consistently demonstrated their safety and effectiveness [4][5][6][7][8][9][10][11]. Most importantly, OEND participation is associated with improved ability of participants to respond appropriately to overdose and safely administer naloxone in order to prevent fatal overdoses [12].…”
Section: Introductionmentioning
confidence: 99%
“…The stated aim of the study was to develop increased understanding of the knowledge and skills that opioid users require and use in overdose emergencies 2. This qualitative study supplements a randomised controlled trial in which people aged 21–65 years meeting the criteria for opioid use disorder within 6 months of the intervention were provided with THN.…”
Section: Methodsmentioning
confidence: 99%